Dissolution Rates of Calcium Boluses and Their Effects on Serum Calcium in Dairy Cattle - Verhoef W (Dove Medical Press, 2021)
Walter Verhoef,1 Sjoert Zuidhof,2 Brenda Ralston,3 Joseph A Ross,4 Merle Olson5 1Bureau Vétérinaire de Richmond, Richmond, Quebec, Canada; 2Sjoert Zuidhof Consulting, Okotoks, Alberta, Canada; 3Alberta Agriculture and Forestry, Airdrie, Alberta, Canada; 4Chinook Contract Research Inc., Airdrie, Alberta, Canada; 5Alberta Veterinary Laboratories, Calgary, Alberta, CanadaCorrespondence: Walter VerhoefBureau Vétérinaire de Richmond, 44 Rue Des Cèdres, Richmond, QC, J0B 2H0, CanadaTel +1 819-212-4091Email verhoefw@videotron.caPurpose: Calcium supplement boluses vary greatly in content and bioavailability.Methods: In vivo dissolution and bioavailability studies were conducted to compare commercial calcium supplement boluses with various contents of calcium chloride and calcium carbonate. The products studied included: Bolus 1 (high calcium chloride, no calcium carbonate), Bolus 2 (medium calcium chloride, medium calcium carbonate), and Bolus 3 (low calcium chloride, high calcium carbonate). A bolus was placed in a pre-weighed coarse mesh net for 30, 60, 90, 120, 180, and 240 minutes to measure dissolution rates in the rumen of fistulated animals. To measure calcium uptake, 27 Holstein cows (second and third lactation) were randomly allocated to one of three oral calcium protocols: Treatment 1 (two high calcium chloride boluses at time 0); Treatment 2 (one high calcium chloride bolus at time 0 with a second bolus 12 hours later); or Treatment 3 (two high calcium carbonate boluses at time 0). Treatments were initiated within 12 hours following calving and this was considered time 0.Results: Bolus 1 was the quickest to dissolve (< 90 minutes), followed by Bolus 2 (< 240 minutes). The high calcium carbonate bolus (Bolus 3) remained after 240 minutes in vivo with a minimum of 75% of the original bolus weight still intact. Cows with severe hypocalcemia (< 1.8 mmol/L) responded with a higher serum calcium increase than cows with milder hypocalcemia (> 1.8 mmol/L, < 2.12 mmol/L). The high calcium carbonate bolus group (Treatment 3) did not show a rapid increase in serum calcium as compared to the high calcium chloride groups (Treatments 1 and 2). The animals receiving Treatment 1 had a greater and more persistent serum calcium response than animals receiving Treatment 2.Conclusion: The study outcome suggests that calcium chloride/calcium sulfate boluses are more effective at generating a serum calcium response than boluses containing high amounts of calcium carbonate and that two boluses administered rapidly after calving may be more effective than the traditional treatment of giving 2 boluses 12 hours apart.Keywords: sub-clinical hypocalcemia, milk fever, calcium chloride, calcium carbonate, calcium bolus, dissolution